2023
DOI: 10.1111/1365-2435.14395
|View full text |Cite
|
Sign up to set email alerts
|

The plant–mycorrhizal fungi collaboration gradient depends on plant functional group

Abstract: Plant colonization by arbuscular mycorrhizal fungi (AMF) is widespread and can offer considerable benefits in terms of growth, nutrient uptake and plant yield. However, it is still unresolved how different plant species and plant functional groups respond to AMF and to different AMF taxa. Here we established 336 grassland microcosms to determine the response of 14 plant species displaying contrasting functional groups (grasses, legumes and non‐leguminous forbs) for the presence of three different AMF taxa. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 112 publications
1
9
0
Order By: Relevance
“…Our results demonstrating the important role of pH as driver of AMF diversity distribution between grassy ecosystems in Argentina and Brazil are consistent with those previously reported for bacteria and other fungi [136] and for protists [137], although both studies identified precipitation as an important additional driver. Moreover, pH has been found as the shaper of AMF diversity worldwide [120,121,131,[133][134][135], in agreement with the AMF community's behavior analyzed in South America for grasslands and pastures in this work. At the same time, it is clear that there remain unmeasured factors that may be important drivers of AM fungal performance or may underlie associations with other variables, such as those identified here [135,138].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results demonstrating the important role of pH as driver of AMF diversity distribution between grassy ecosystems in Argentina and Brazil are consistent with those previously reported for bacteria and other fungi [136] and for protists [137], although both studies identified precipitation as an important additional driver. Moreover, pH has been found as the shaper of AMF diversity worldwide [120,121,131,[133][134][135], in agreement with the AMF community's behavior analyzed in South America for grasslands and pastures in this work. At the same time, it is clear that there remain unmeasured factors that may be important drivers of AM fungal performance or may underlie associations with other variables, such as those identified here [135,138].…”
Section: Discussionsupporting
confidence: 87%
“…Our results demonstrating the important role of pH as driver of AMF diversity distribution between grassy ecosystems in Argentina and Brazil are consistent with those previously reported for bacteria and other fungi [136] and for protists [137], although both studies identified precipitation as an important additional driver. Moreover, pH has been found as the shaper of AMF diversity worldwide [120,121,131,[133][134][135], in agreement with the AMF community's behavior analyzed in South America for grasslands and pastures Local environmental conditions and the spatial distance between sites are also important drivers of AMF community structure [117][118][119]. In line with this, Hazard et al [120] demonstrated that landscape-scale distribution of AMF taxa is driven by the local environment, especially by abiotic factors, including pH, rainfall, and soil type [120,121].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that other plant traits (e.g., specific root length or root diameter) that likely co-vary with symbiosis type also influence root microbiome composition [reviewed in 45 ]. For instance, a recent study demonstrated that grasses have a higher specific root length (e.g., longer roots per gram root) compared to herbs and legumes [ 46 ]. However, as most of the plant species included in our present study are herbs and legumes, it is less likely that differences in specific root lengths were a major driver of changes in microbiome composition.…”
Section: Discussionmentioning
confidence: 99%
“…The data further corroborate that plant biomass is positively correlated with the uptake of N, P, and K + (Figure S2). Generally, mycorrhizal benefits for plant growth are mainly ascribed to the mycorrhiza-mediated improvement in plant P [22,60]. However, the present study showed that mycorrhizal efficiency was mainly enhanced by N uptake (Figure 7D), which may be because C. camphora seedlings were exposed to N limitation during biomass production (Figure 5) [61].…”
Section: Mycorrhizal Efficiency On Plant Biomassmentioning
confidence: 56%